Skepping en evolusie: 'n filosofiese besinning oor tyd, ruimte en materie - P. H. Stoker (Acta Theologica)
This philosophical reflection on time, space and matter in the debate creationevolution accepts that the universe came into existence as a number of acts of deliberate supernatural creation by an already existing God. Since the first human couple was created on the sixth day, the creation evolves in all spheres of life with time passing by. Accepting time linearity and physical uniformitarianism, disregarding supernatural acts and catastrophes, natural sciences reconstruct the past from the present. The result is ages of thousands of million years for the earth and early life,and for a universe, having a size in terms of this number of light-years. None of these assumptions and results can be verified. Physical evolution requires theoretical explanations beyond the very limited observational data at our disposal and cannot be considered as revealed truth. Furthermore, naturalism is inherent in modern science and cannot explain the full richness of our experienced reality.